Animasi Interaktif Pengenalan Huruf Hijaiyah Berbasis Android - Rizky Januar Yudhistira; Widiarina Widiarina (JURNAL TEKNIK KOMPUTER AMIK BSI, 2019)
The development of animation that occurred in this era is very rapid. Animation is now an alternative in conveying the intent and purpose of information in digital media that is often used on computers and smartphones. As Muslims it is important to learn the Hijaiyah letter in the form of Arabic, because it is the beginning of the beginning of learning in Arabic sentences, and also in the fluent reading of the Qur'an along with its punctuation marks. Android smartphone users at this time are very diverse, including parents, young people, and children, but seeing in terms of function and benefits, smartphones can be interactive digital media that is useful and useful in knowing new knowledge and adding insight. In this case the author designs interactive animations to recognize letters and numbers hijaiyah and is equipped with games that are expected so that children do not get bored quickly, exercise memory, and are easy to understand. The method used in the development of this software uses the waterfall model. The concept of the animation system is made into a practical application and as an intermediary medium can be run on their gadgets